Função materna e função paterna, suas vivências na atualidade - Borges, Maria Luiza Soares Ferreira (2005)
The subject maternal function and paternal function, nowadays refers to a theoretical and a practical investigation concerning the exercise of those functions. The theoretical investigation was developed though the psychoanlysis optics, in the pruning of authors from distinct thoughts tendency, having in common the importance of maternal function (Klein, Bion, Winnicott and Dolto) and paternal function (Freud, Winnicott, Dor and Hurstel) in structuring and development of child psychism, in an atempt to perform their functions as parents since the first stage where they have been conceived and how they follow up children development. The practical investigation concerns psychoanalytic interviews with four couples with children among zero to five years old, in order to observe, map and consider their experiences in their roles as parents, from their perception, as well as on how they have been structuring their lives in accordance to the great changes in the lives of men and women nowadays. In the elaboration and writting of this essay, it was used the method of self organization of psychoanalytic inspiration (Baccarin). When mapping and considerating the parent s experiences in their roles I could notice that to become a parent starts gradually since conception and even before, when there is the desire of pregnancy, and the contact between partners, their child and society, throughout an intergame of conflicts and anxieties enlarged by todays enourmous world demands that takes them to a state of deep emotional turbulance, and many times a sense of unauthorization of parenting experiences. Due to world s demands, parents count on a partnership between them (co-parenting), which their roles are performed according to their psychoafectiveability, differently from the strictly defined roles in the past. This fact seems to make men closer to their children since they are born, a fact that was considered to be exclusivity of women s. On the other hand, women seem to be living an earlier interruption of their intimate contact with their babies due to the demand of several facet of a woman s role, among them their work. Thus the function has been distributed among father, relatives and school. The interest on investigating this theme is the possibility of a reflection that can be useful to the work of educators and clinic psychologists, specially on what it concerns parents listening and orientation.